2018
DOI: 10.7717/peerj.4777
|View full text |Cite
|
Sign up to set email alerts
|

The effect of climate change on the distribution of a tropical zoanthid (Palythoa caribaeorum) and its ecological implications

Abstract: Palythoa caribaeorum is a zoanthid often dominant in shallow rocky environments along the west coast of the Atlantic Ocean, from the tropics to the subtropics. This species has high environmental tolerance and is a good space competitor in reef environments. Considering current and future scenarios in the global climate regime, this study aimed to model and analyze the distribution of P. caribaeorum, generating maps of potential distribution for the present and the year 2100. The distribution was modeled using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 82 publications
1
14
0
Order By: Relevance
“…Even though the effects of each environmental variable on the population dynamics are unknown [101], the variables chosen to model the habitat suitability for M . harttii are in accordance with default conditions in previous studies on anthozoans [102].…”
Section: Discussionsupporting
confidence: 89%
“…Even though the effects of each environmental variable on the population dynamics are unknown [101], the variables chosen to model the habitat suitability for M . harttii are in accordance with default conditions in previous studies on anthozoans [102].…”
Section: Discussionsupporting
confidence: 89%
“…Projecting future changes in the composition of species in reef ecosystems, albeit essential, is also challenging. Species distribution modeling (SDM) has become an important tool for ecologists [see Elith and Leathwick (2009) for a complete review], enabling predictions of current and future habitat suitability for a certain species (Cacciapaglia and van Woesik, 2018;Durante et al, 2018;Morato et al, 2020). These models incorporate the current empirical distribution of a given species (gathered from geolocated presence and absence data from surveys and global databases) and environmental data to establish habitats with the necessary conditions for that species to survive (Pearson and Dawson, 2003;Pearson et al, 2006;Wiens et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that changes in pH conditions not only reduce calcification rates but also alter many physiological mechanisms in marine species (Arnold et al, 2012; Li & Gao, 2012). In fact, predicted models based on habitat suitability of P. caribaeorum in the West Atlantic suggested that 7.85 units of pH might be a barrier to its distribution pattern (Durante, Cruz & Lotufo, 2018). Biological performance of zooxanthellate zoantharians is highly mediated by the status of their symbionts, since species sustenance strongly depends on nutrients photosynthesized by Symbiodiniaceae.…”
Section: Discussionmentioning
confidence: 99%
“…also leads to modification of the composition of associated mesofauna (González‐Delgado et al, 2018) and even the whole intertidal and subtidal landscapes (López et al, 2020). In a climate change context, zoantharians may become ecologically dominant species to the detriment of other sessile organisms (Reimer et al, 2008; Durante, Cruz & Lotufo, 2018), compromising native ecosystems’ biodiversity and function.…”
Section: Introductionmentioning
confidence: 99%